Collection development plan and policy for the Arayat Central Elementary School library - Manabat, Elisa Joan S.; Santos, Mark Anthony A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
This study was conducted to help the Arayat Central Elementary School, one of the leading primary schools in Pampanga, to have a functioning library. A total of 140 respondents (120 students and 20 teachers) were surveyed to determine the needs and interests of the future clientele. An interview with the principal was conducted separately.
The data gathered from the interview and survey questionnaires revealed that: (a) Math, English, HEKASI and Science were the most sought subjects in school by the students while for teachers, HEKASI, English and Home Economics were the most sought; (b) 60% of the students were aware that there is no attending librarian/staff inside the library while a massive 95% from the faculty members; (c) 40% of the students' population is not interested in reading and; (d) 67.5% of the students believe that a library can help them study well and 90% of the faculty members agreed that if the library can be fully utilized, it will be easier for them to educate the next generation.
Recommendations were given such as: (a) weed out all the outdated and inappropriate materials present inside the library; (b) hire a staff and a licensed teacher-librarian; (c) acquire fresh and updated materials such as books, novels and short stories to persuade the clients to read; (d) increase the number of collection towards the subjects Math, English, HEKASI, Home Economics and Science; and (e) follow the development plan created for ACES Library, the collection development policy and the floor plan.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Collection development (Libraries) -- Philippines -- Pampanga